If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 2(x + -1(5 + -4x)) + 4 = 3x 2(x + (5 * -1 + -4x * -1)) + 4 = 3x 2(x + (-5 + 4x)) + 4 = 3x Reorder the terms: 2(-5 + x + 4x) + 4 = 3x Combine like terms: x + 4x = 5x 2(-5 + 5x) + 4 = 3x (-5 * 2 + 5x * 2) + 4 = 3x (-10 + 10x) + 4 = 3x Reorder the terms: -10 + 4 + 10x = 3x Combine like terms: -10 + 4 = -6 -6 + 10x = 3x Solving -6 + 10x = 3x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-3x' to each side of the equation. -6 + 10x + -3x = 3x + -3x Combine like terms: 10x + -3x = 7x -6 + 7x = 3x + -3x Combine like terms: 3x + -3x = 0 -6 + 7x = 0 Add '6' to each side of the equation. -6 + 6 + 7x = 0 + 6 Combine like terms: -6 + 6 = 0 0 + 7x = 0 + 6 7x = 0 + 6 Combine like terms: 0 + 6 = 6 7x = 6 Divide each side by '7'. x = 0.8571428571 Simplifying x = 0.8571428571
| 0.6t-0.1=0.5+0.2 | | 0.5x+2y=k | | 6x-[2x-(x-8)]=10-x | | -7(x+4)=35 | | 10x+9=45 | | 3w-5+2(3w+3)=(-3)(w+5) | | -4x+0x= | | 4-y^2=403(y-2) | | x^2-3x+12=1 | | 4+-x= | | 2x-2(x+19)=2x-3(7+x) | | x+(-33)=39 | | 7=r-9s | | 4x+-0x= | | -4n+5=17 | | 2x+17=31 | | -4+x= | | r^2-5=-4r | | 48=5u-12 | | x^2-y^2=403(y-x) | | -4n+5=15 | | 2[x-(5-4x)]+4=3x | | 6b^2c^3+6b^3c^2-3b^3c^2= | | 9/3(6x*4/8) | | (-2)(-7y+4)-3y=5(y-2)-7 | | 3n-(9+n)= | | 9-3r=-14 | | w+5.34=5.39 | | 5c^2-40c=4125 | | 0.38x+0.44(7)=0.4(x+7) | | -10x=210 | | (-5)v-1=7(v+5) |